2021
DOI: 10.1002/crat.202000182
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size and Crystal Habit Modification of Active Pharmaceutical Ingredient Using Cooling Sonocrystallization: A Case Study of Probenecid

Abstract: This study uses a cooling sonocrystallization process to recrystallize an active pharmaceutical ingredient, probenecid, and to improve the crystal qualities such as crystal habit and particle size characteristics. To screen the appropriate solvent system, solubility data of probenecid in organic solvent are measured, reported, and correlated by van't Hoff equation. According to the measured solubilities and data acquired from literature, sonocrystallization experiments using solvents with acceptable theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, compared with the ultrasonic bath, the ultrasonic horn has a stronger cavitation effect, and thus the crystal prepared using the ultrasonic horn has better properties. Chang et al 58 found that probenecid crystals prepared by conventional cooling crystallization were in a disordered needle-like state, while after ultrasonic treatment, regular rod-like probenecid crystals with a small crystal size and narrow particle size distribution were obtained. Under the same cooling rate and ultrasonic conditions, the particle size of probenecid crystals could be increased from 9.4 μm to 15.3 μm, as the solution concentration increased from 45 mg mL −1 to 90 mg mL −1 .…”
Section: Intensification Of Crystal Growthmentioning
confidence: 99%
“…In addition, compared with the ultrasonic bath, the ultrasonic horn has a stronger cavitation effect, and thus the crystal prepared using the ultrasonic horn has better properties. Chang et al 58 found that probenecid crystals prepared by conventional cooling crystallization were in a disordered needle-like state, while after ultrasonic treatment, regular rod-like probenecid crystals with a small crystal size and narrow particle size distribution were obtained. Under the same cooling rate and ultrasonic conditions, the particle size of probenecid crystals could be increased from 9.4 μm to 15.3 μm, as the solution concentration increased from 45 mg mL −1 to 90 mg mL −1 .…”
Section: Intensification Of Crystal Growthmentioning
confidence: 99%